The Potency of Polygamy Behavior in Aedes aegypti Mosquitoes by Venereal Transmission Dengue Virus - Putri, Devita Febriani; Widya, Asmara; Sugeng, Mardihusodo Juwono; Sitti, Ummiyati Rahmah (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Male Aedes aegypti mosquito has been considered to not have any important role in transmitting dengue virus (DENV). The purpose of this study is to prove that male Ae. aegypti mosquito does have an important role in transmitting DENV 3 through venereal transmission with their potency of its polygamy behavior. The data collection was done using colonization method and intrathoracal injection. The presence of DENV 3 on male and female mosquitoes was proven by RT-PCR method (profile of DNA band specifically on 511 bp) and serotyping PCR (290 bp). The data were analyzed using univariate analysis followed by bivariate analysis with parametric test ANOVA. The result of the study demonstrated that male Ae. aegypti mosquitoes do have an important role in transmitting DENV 3 through venereal transmission with the potency of their polygamy behavior. There was no significant difference between the polygamy behaviors of Ae. aegypti male mosquito infected by DENV and the non-infectious Ae. aegypti male mosquito.